Mesocarp-specific promoter for oil palm genetic modification - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2006)
Genetic engineering provides avenues for diversification to Increase the economic value of palm oil. Production of speciality oils for industrial applications will be a very attractive proposition for the oil palm, since it is a very productive oil crop. This is considered a useful strategy to maximize income in the midst of problems of labour shortage. high labour cost and lack of arable land for expansion. The success of any genetJc engineering efforts relies on the availability of the following: Genes to produce the desired traits; Regulatory sequence or promoter for controlling expression of introduced genes; Reliable transformation technique; Plant regeneration system.